Evolution Laws of Stress–Energy and Progressive Damage Mechanisms of Surrounding Rock Induced by Mining Disturbance - Jinzheng Bai; Linming Dou; Xuwei Li; Xiaotao Ma; Fangzhou Lu; Zepeng Han (Applied Sciences, 2023)
The rock burst induced by the mutual disturbance of mining and excavation is significantly influenced by high static load stress and external dynamic load disturbance. In this paper, the evolution characteristics and progressive damage mechanism of surrounding rock in the process of mutual disturbance of mining and excavation are systematically studied. The results show that the evolution of surrounding rock stress can be roughly divided into three stages: rapid rise in the early stage, continuous rise and step-like decline in the middle stage, and slow rise in the late stage. In the process of parallel mining, the overlying rock movement above the goaf shows the sequence of horizontal penetration of tiny fissures—fracture intensification transition to stratification—non-coordinated caving of middle–low overlying rock—obvious horizontal cracks in the upper key layer. Only under the quasi-static loading mining action does the upper key layer not reach the breaking condition. The wave side of the heading face which is close to the focal point is affected by the dynamic load disturbance, the acceleration duration is short, and the attenuation is relatively fast, so it is the area prone to the earliest impact failure in the face of mining disturbance. The conclusion is helpful to deepen the understanding of the coal burst mechanism of mutual disturbance of mining and excavation.